(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
This research focuses on Rub subtype verbs in and English Konjo language. The aims of the research were (1) to identify Rub subtype verbs in Konjo language and English. (2) to investigate the similarities and the differences of Rub subtype verbs in English and Konjo language in the aspect of semantic and grammatical construction. Furthermore, this research used descriptive qualitative method. English data were taken from COCA (Corpus of Contemporary American English). Meanwhile, Konjo language data were taken from observation and interview. Then, the results of this research indicated that (1) there are twelve Rub subtype verbs in English: rub, wipe, scrape, scratch, mark, sweep, brush, shave, rake, polish, lick and wash. Then, in Konjo language, there are nineteen verbs of Rub subtype: a’goso’, assossoro, angngampallasa, a’lu’lu’, angnga’ru’ akkankang, angngara’musu, annanrai, a’ca’ a’barrasa, assika’, accukkuru, kokkoro, assumer, a’lemong, angngemu’, a’bissa, assassa, and angngi’lasi. (2) The similiarities and the differences of Rub subtype verbs in English and Konjo language: The similarities are both of Rub subtype verbs in English and Konjo language can be applied in construction I (Agent + Target + Manip) and construction II (Agent + Manip + Target). The differences are the variant construction of English Rub subtype verbs and the extra constructions of Konjo language Rub subtype verbs. The variant construction of English Rub subtype verbs is variant construction Ib (Agent + Target (Adj) + Manip) and extra constructions of Konjo language are extra construction Ia (Agent + Target), Ib (Target + Agent), Ic (Agent + Target + Agent), Id (Agent), Ie (Target + Agent)*, IIa (Agent + Target + Manip)*, IIb (Manip + Agent + Target), IIIa (Manip + Target + Manip) and IIIb (Manip + Manip + Target).